A single centre experience of squamous cell carcinoma of the upper limb requiring digital or hand amputation and review of literature. (June 2019) - Sayed, Leela; Deodhar, Avinash K.; Agarwal, Reena
Abstract: Squamous cell carcinoma (SCC) is one of the most common primary malignancies affecting the upper limb. A range of treatment options exist for its management; amputation being indicated under certain instances. This is the first comprehensive case series and review of the literature reporting outcomes following amputation of the affected region for treatment of upper extremity SCC. We present a series of six patients with squamous cell carcinoma of the upper limb that required amputation alongside that of data from literature review. Patient demographics, risk factors, tumour characteristics and rates of recurrence, metastasis and mortality were recorded. A total of 45 patients with 49 histologically confirmed squamous cell carcinomas were identified from case series and literature review. Patients presenting with upper limb SCC were predominantly male and in their sixth decade of life. Mean follow up time was 30.5 months and the overall recurrence and metastatic rates were 8.2% and 14.3%, respectively. Mortality was 14.3% however only 6.1% was related to SCC metastasis. Rates of recurrence and metastasis are higher for SCCs affecting the hand as compared to other body sites. Furthermore, different regions of the hand appear to behave differently. SCC affecting the nail unit has a high recurrence and a low metastatic rate, whereas, SCC involving the palm and webspaces are aggressive and this is true despite amputation of the affected site.